The Language Function on Youth's Motivating Discourse - Nugroho, Abdillah; Wahyudi, Agus Budi; Sunanda, Adyana; Sabardila, Atiqa; Faizah, Naimul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
Purpose: This research was aimed at identifying the language function on youth’s motivating discourse. . It was carried out by describing the language function on youth’s motivating discourse.Methodology: The research belonged to qualitative research. The primary data were the language functions on youth’s motivating discourse. Technique of the data collection was documentation by collecting the students’ writings at SMP Muhammadiyah 6 Surakarta, such as motivating discourse, particularly discourse containing the language function. Technique of the data analysis was done by making use of the referencial and critical reading technique and small groud discussion.Results: The research result found 4 functions of the language on youth’s motivating discourse, such as (1) the instrumental function i.e. order, offer, and request, (2) the personal function that describes emotion, spirit, happiness, good mood, (3) the representation function, and (4) the regulation function.